Holographic Acoustic Tweezers for 5-DoF Manipulation of Nanocarrier Clusters toward Targeted Drug Delivery - Hiep Xuan Cao; Daewon Jung; Han-Sol Lee; Van Du Nguyen; Eunpyo Choi; Byungjeon Kang; Jong-Oh Park; Chang-Sei Kim (MDPI AG, 2022)
Acoustic tweezers provide unique capabilities in medical applications, such as contactless manipulation of small objects (e.g., cells, compounds or living things), from nanometer-sized extracellular vesicles to centimeter-scale structures. Additionally, they are capable of being transmitted through the skin to trap and manipulate drug carriers in various media. However, these capabilities are hindered by the limitation of controllable degrees of freedom (DoFs) or are limited maneuverability. In this study, we explore the potential application of acoustical tweezers by presenting a five-DoF contactless manipulation acoustic system (AcoMan). The system has 30 ultrasound transducers (UTs) with single-side arrangement that generates active traveling waves to control the position and orientation of a fully untethered nanocarrier clusters (NCs) in a spherical workspace in water capable of three DoFs translation and two DoFs rotation. In this method, we use a phase modulation algorithm to independently control the phase signal for 30 UTs and manipulate the NCs' positions. Phase modulation and switching power supply for each UT are employed to rotate the NCs in the horizontal plane and control the amplitude of power supply to each UT to rotate the NCs in the vertical plane. The feasibility of the method is demonstrated by in vitro and ex vivo experiments using porcine ribs. A significant portion of this study could advance the therapeutic application such a system as targeted drug delivery.